The Implementation of Group Investigation to Improve the Students’ Speaking Skill - Iswardati, Iswardati (Dinamika Ilmu: Jurnal Pendidikan, 2016)
This research aimed to find out how group investigation improves the student’s speaking skill of the second grade students of SMA 2 Samarinda, how group investigation improves the student’s participation in speaking of second grade students of SMA 2 Samarinda, and what the obstacles are in the implementation of Group Investigation. The classroom action research was employed in this study and was done in two cycles. Each cycle consisted of four stages: (1) planning, (2) action, (3) observation, and (4) reflection. Each cycle took three meetings. The instruments used to collect the data were observation, checklist, field-note, and speaking test. After the implementation of Group Investigation through two cycles, the researcher concluded: First, Group Investigation improves the students’ speaking ability by (a) increasing the students’ pronunciation, grammatical, vocabulary, and fluency, (b) by reducing the students’ reluctance to speak, worry of making mistakes, and afraid of being laughed at by other students. Second, Group Investigation improves the students’ participation in speaking (a) the students learnt how to investigate a certain problem and to solve the problem using English, (b) how to share, (c) how to discuss, (d) how to give their ideas, (e) how to accept other opinions, and (f) how to present their ideas. Third, the obstacles in the implementation of Group Investigation are: (a) The students were noisy, (b) Some students spent too short in the presentation, (c) Some students had difficulties in expressing their arguments and suggestion related to the topics, and (d) Few students dominated the group investigation.